Hazard Identification and Safety Education on The Clothing Convection Industry Business in Semarang - Purboeningrum, Amanda Desti; Dimas, Sifa Sabani; Febriananda, Hanif Satria; Oktriyani, Sharon; Ananto, Favian Anggorokasih Putra; Wulandari, Ririn; Hikmahyanti, Hikmahyanti (Universitas Negeri Semarang, 2024)
The clothing convection industry is one of the most popular businesses, with many growing businesses in Indonesia. In this industry, there are potential hazards that may occur either from work environment factors, the use of tools or machines, or from workers. Research objective to be achieved is to identify potential hazards in the clothing convection industry X and Y. This research used descriptive research, and the sample was two workers at the clothing convection industry X and four workers at the clothing convection industry Y for the data. The sample selection used random sampling. The data analysis technique used a narrative analysis. To minimize the number of work accidents or prevent accidents in the workplace, the identification of potential hazards is carried out through hazard analysis methods; one method is HAZOPS (Hazard Operability Studies). Based on the results of identification from workers and observation using HAZOPS method to minimize potential danger that can occur in each production with safety education using video to convey information easily for workers. Education on the use of PPE is also provided so that workers have safety knowledge and awareness at work. X and Y convection have various potential dangers in the clothing convection industry. Therefore, immediate action and attention from management are needed to minimize work accidents.